Infrared and Thermal Studies of Some Six-Coordinated Zirconium(IV) Complexes of Schiff Bases of 4-Aminoantipyrine† - Singh, Lakshman; K. Manglik, Ajay; Pal Dhaka, Naresh (Asian Journal of Chemistry, 2010)
In the present investigation, we wish to report the synthesis of some six-coordinated zirconium(IV) complexes of Schiff bases derived from 4-aminoantipyrine with the general composition [Zr(OH)2L2]Cl2, where L = 4 [(N-benzalidene)amino]antipyrine, 4[(N-p-diaminobenzalidene)amino]antipyrine, 4[(N-2-hydroxybenzalidene) amino]antipyrine, 4[(N-p-methoxybenzalidene )amino] antipyrine, 4 [(N-4-hydroxy-3-methoxybenzalidene)amino]antipyrine, 4[(N-2-hydroxy-1-naphthalidene)amino]antipyrine, 4-[(N-cinnamalidene)amino]-antipyrine, 4[(N-(3,4,5-trimethoxyben zalidene )amino)]-antipyrine and 4[(N-furfural)amino]antipyrine. All the complexes were characterized by elemental analysis, conductance, molecular weight and infrared. The IR data of the complexes reveal the bidentate nature (O, N) of the ligand. The probable coordination number of zirconium(IV) is found to be six in the present complexes. Thermal data suggest the presence of coordinated water molecule in the complexes.